Narrative Online Advertising as External Variable in the Development of the Technology Acceptance Model of Go-Pay for Millennials - Sugeng Purwanto; Sri Hartini; Gancar Candra Premananto (JASF: Journal of Accounting and Strategic Finance, 2020)
Human life is inseparable from technological developments. Until now, research related to the Technology Acceptance Model (TAM) is still used as a basis for the theory of technology product acceptance in line with the increasingly complex development of human behavior and needs. This research is the development of Technology Acceptance Modeling (TAM) by involving the Narrative Online Advertising variable. The purpose of this study is to develop and test the model by including the Narrative Online Advertising variable as an external variable or antecedent variable to the attitudes and intentions of millennials in adopting an electronic wallet (Go-Pay). The Narrative Online Advertising variable, as the theory developed by Ching, Tong, Chen, & Chen, is an online advertising strategy involving the narrative element in advertising content, which has been widely displayed on the internet media. The object used in this study is Go-pay, a popular electronic wallet application in Indonesia. The sample in this study is the millennial communities domiciled in Surabaya totaling 200 respondents, collecting data through questionnaires, using a Likert scale, and the analytical tool used is SmartPLS. The results of this study show that Narrative Online Advertising has a positive effect on the Perception of Ease of Use, but does not affect the Perception of Benefits. At the same time, the four factors positively affect the Attitude and intention to adopt Go-pay. These results indicate that millennials will use Go-pay if Narrative Online Advertising is improving their interest in using the e-wallet. Therefore, it is suggested that in making an e-money application, Narrative Online Advertising is important to attract millennials in using the app.